44.8k views
3 votes
Write the quadratic equation in standard form and then choose the value of "b."

(2x - 1)(x + 5) = 0
O
10
011
pllllllls help me

User LPs
by
4.4k points

2 Answers

3 votes


(2x-1)(x+5)=2x^2+9x-5=0.

The quadratic equation has a general form of


ax^2+bx+c=0.

So your "b" is 9.

Hope this helps.

User Fitzroy
by
4.6k points
6 votes

Answer: Answer is in the steps

Explanation:

(2x-1)(x+5) = 0 First expand the left side by apply the distributive property twice.

(2x -1)(x+5) =0

x(2x -1) = 2x^2 -1x

5(2x -1) = 10x -5

Now rewrite them all together

2x^2 - 1x +10x -5 = 0 combine like terms on the left side.


2x^(2) + 9x -5 = 0 a is the first leading coefficient,b is the second leading coefficient, and c is the constant.

So in this case, the value of b is 9.

User AlKozin
by
5.2k points